PEMBUATAN DAN PENERAPAN TEKNOLOGI PRESS SERBAGUNA UNTUK MENDUKUNG PEMBUATAN SIRUP - Yohanes B. Yokasing; Amiruddin Abdullah; Mamiek Mardyaningsih (Dedication : Jurnal Pengabdian Masyarakat, 2018)
Pure cashew fruit has not been processed to the maximum, due to technological limitations between shreds and presses, and limited human resources. For that we need to develop a versatile press technology capable of doing shreds and press. Shredding of fake fruit flesh aims to juice mente that is in the fruit can be liberated during the press. Juice from cashews this cashew fruit, used as cashew syrup. Versatile press technology successfully created, has the following specifications, height: 1600 mm, width 460 mm, manual power, motion inputted through the wheels shrink press, capacity 10 kg once process, production ± 1 liter per 3 minutes. This Multipurpose Press is applied to the activity of Cashew Processing service in Ipteks bagi Kreativitas Inovasi Kampus (IbKIK) at Politeknik Negeri Kupang.